Lecturer Perceptions of General Education in Enhancing Self-Efficacy of Accounting Students - Naidoo, Suntharmurthy Kristnasamy; Govender, S. (Journal of Education and Vocational Research, 2021)
The research paper aims to obtain the perceptions of lecturers on the influence of General Education in enhancing the Self-efficacy of accounting learners. Interviews with lecturers from Durban University of Technology (DUT) and Mangosuthu University of Technology (MUT) were conducted to tap into their views on the aspect of General Education and establish y impact on learners’ Self-efficacy. The researcher has observed, over many years of lecturing experience at the university that some learners are eager to learn and can address new tasks, while others appear uninterested or unmotivated. Many learners display a high degree of faith in their skills, while others appear uncertain of themselves. The question then arises: What strategies can a classroom teacher or lecturer use to increase learners’ confidence to learn new material? There is an opportunity for the improvement of General Education skills that can enhance learner performance. Hence, the main strategy would be to incorporate General Education Modules into the curriculum. Similar to General Education skills, there is also a lack of Self-efficacy in current learners. Further attention must be devoted to General Education skills, as these are essential. Moreover, these skills appear to be very poor amongst current learners and respondents believed that Self-efficacy could have a positive effect on the academic performance of learners. Methods for enhancing Self-efficacy reveal that the main strategies should revolve around innovative teaching, learning and research methods; increasing skills development such as critical thinking and computer skills; and promoting more Self-efficacy based workshops and programs.